Pax9’s Interaction With the Ectodysplasin Signaling Pathway During the Patterning of Dentition - Jia, Shihai; Oliver, Jeremie D.; Turner, Emma C.; Renouard, Maranda; Bei, Marianna; Wright, J. T.; D’Souza, Rena N. (Frontiers in Physiology, 2020)
In these studies, we explored for the first time the molecular relationship between the paired-domain-containing transcription factor, Pax9, and the ectodysplasin (Eda) signaling pathway during mouse incisor formation. Mice that were deficient in both Pax9 and Eda were generated, and the status of dentition analyzed in all progeny using gross evaluation and histomorphometric means. When compared to wildtype controls, Pax9+/–Eda–/– mice lack mandibular incisors. Interestingly, Fgf and Shh signaling are down-regulated while Bmp4 and Lef1 appear unaffected. These findings suggest that Pax9-dependent signaling involves the Eda pathway and that this genetic relationship is important for mandibular incisor development. Studies of records of humans affected by mutations in PAX9 lead to the congenital absence of posterior dentition but interestingly involve agenesis of mandibular central incisors. The latter phenotype is exhibited by individuals with EDA or EDAR mutations. Thus, it is likely that PAX9, in addition to playing a role in the formation of more complex dentition, is also involved with EDA signaling in the initiation of odontogenesis within the incisal domain.